A Multivariate Model Explaining Men's Violence Toward Women - O'Neil, J. M. (Violence against women, 1997)
Violence against women by men is considered the single most serious threat to women's health and welfare in the United States. Knowledge about why male violence occurs against women is very limited. Previous theory and conceptualizations explaining men's violence have narrowly focused on individual factors or typologies. Predicting male violence is complex, necessitating a multivariate explanatory model. No heuristic model has been developed that explains the multiplicity of hypotheses that might explain men's violence toward women. This article presents a multivariate model explaining men's violence toward women using four content areas and 13 hypotheses. The content areas are: (a) macrosocietal explanation; (b) biological, neuroanatomical, hormonal explanation; (c) gender role socialization or gender role conflict explanation; and (d) intergender, relational explanation. Implications of the model for educational interventions, research, and training are explored